Exploring the integration of grade 8 history curriculum through Bernstein’s Theoretical Concepts of Classification and Framing - Thulo, Atang (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Curriculum integration has become one of the transformative approaches in modern education systems that aim to foster meaningful, connected learning experiences among students. Instead of teaching subjects as separate entities, integrated curricula present subjects in ways that enhance understanding and relevance to students’ lives. Therefore, this paper examines the integration of the Grade 8 History curriculum through Bernstein’s theoretical concepts of classification and framing, focusing on the extent of integration between discourses and control relations in the instructional process, especially regarding content and pedagogy. This study used an explanatory sequential mixed-methods design, with qualitative explanations following quantitative results for deeper insight. Purposive sampling was used to select content and pedagogy for assessing the level of integration. The findings reveal weak classification of content and weak framing in the pedagogy of the Grade 8 History curriculum. The study concludes that there is a high level of integration between discourses and control relations in the instructional process, as analyzed through Bernstein’s theoretical framework, based on content and pedagogy. It recommends that the Ministry of Education and Training offer ongoing professional development to equip teachers with the necessary skills for successful curriculum implementation and to reform pre-service teacher education programs accordingly. The study also suggests reviewing the Grade 8 curriculum, as it emphasizes Western content more than African
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 8, Volume 9, 2025
Keywords: Classification; Content analysis; Content; Document analysis; Framing; Pedagogy; Classification; Document clustering; Teaching; Curriculum planning; Education -- Curricula; History -- Study and teaching